Hindī-paramārtha - Parāśara, Hari Canda (Bhāshā evaṃ Saṃskrti Vibhāga, Himācala Pradeśa, 1978)
On the cultural heritage of Himachal Pradesh, India, and Hindi grammar, with administrative vocabulary from English to Hindi.